2012
DOI: 10.1155/2012/951025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Endogenous Angiotensin II on Alveolar Fluid Clearance in Rats with Acute Lung Injury

Abstract: These findings suggest that endogenous Ang II inhibits AFC and dysregulates ENaC expression via AT1 receptors, which contribute to alveolar filling and pulmonary edema in LPS-induced ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…LPS increases the levels of AngII which acts through AT 1 R [79]. Thus the effect of Ang-(1-7) on LPS-induced muscle wasting may be due to the fact that Ang-(1-7) antagonizes the direct effect of AngII on skeletal muscle, as we have demonstrated recently [40,41].…”
Section: Discussionmentioning
confidence: 68%
“…LPS increases the levels of AngII which acts through AT 1 R [79]. Thus the effect of Ang-(1-7) on LPS-induced muscle wasting may be due to the fact that Ang-(1-7) antagonizes the direct effect of AngII on skeletal muscle, as we have demonstrated recently [40,41].…”
Section: Discussionmentioning
confidence: 68%
“…Studies have shown that Ang II as an important component of RAS is involved in the pathogenesis of lung injury in different models, and most actions of Ang II are related to the AT1 receptor. Thus, strategies that aim to inhibit Ang II production and/or its receptor have been found to exert protective effects [11,12]. Deng et al [11] found endogenous that Ang II could inhibit alveolar fluid clearance and dysregulate α‐epithelial sodium channel expression via AT1 receptors, which contributed to the alveolar filling and pulmonary edema in lipopolysaccharide‐induced ALI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strategies that aim to inhibit Ang II production and/or its receptor have been found to exert protective effects [11,12]. Deng et al [11] found endogenous that Ang II could inhibit alveolar fluid clearance and dysregulate α‐epithelial sodium channel expression via AT1 receptors, which contributed to the alveolar filling and pulmonary edema in lipopolysaccharide‐induced ALI [11]. In radiation‐induced lung injury, Ang II significantly increased in the lung even at 6 months after irradiation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Na, K‐ATPase plays the role of sodium pump that works in concert with apical ENaC in regulating AFC . A 2 B adenosine receptor agonists, angiotensin, tri‐Iodo‐L‐thyronine and oestradiol have exhibited increasing AFC effects via promoting ENaC or Na, K‐ATPase activity in animal studies . However, these studies remain unsuccessful in humans .…”
Section: Introductionmentioning
confidence: 99%
“…A 2 B adenosine receptor agonists, angiotensin, tri‐Iodo‐L‐thyronine and oestradiol have exhibited increasing AFC effects via promoting ENaC or Na, K‐ATPase activity in animal studies . However, these studies remain unsuccessful in humans . Previously, we reported that administration of a β‐agonist salbutamol (iv) decreased extravascular pulmonary fluid in ALI/ARDS patients.…”
Section: Introductionmentioning
confidence: 99%